URETERITIS CYSTICA: A RARE CASE OF BILATERAL OBSTRUCTION OF THE UPPER URINARY TRACTS - A. Yu. Seroukhov; K. K. Akhmedov; Yu. V. Kemezh (Вестник урологии)
Cystic Ureteritis (ureteritis cystica) is an uncommon pathology characterized by the formation of cysts beneath the mucosa of the upper urinary tract, usually with a diameter of a few millimeters up to a centimeter. They belong to benign conditions and are associated with chronic irritation of the ureter as a result of recurrent infection or urolithiasis. As a rule, this pathology is seldom accompanied by any specific clinical manifestations. They are usually found incidentally during routine radiological investigations of the upper urinary tract. Management involves the treatment of the underlying disease and eradicating any infection. In this article we present a clinical case of a patient with bilateral obstruction of the ureters by intralumenal cystic lesions.